## Solving the Equation: 0 = -3/4x + 25

This article will guide you through solving the equation **0 = -3/4x + 25**. We will walk through each step of the process to find the value of *x*.

### Step 1: Isolate the x term

The goal is to have the *x* term alone on one side of the equation. To do this, we need to get rid of the constant term, **25**.

Subtract **25** from both sides of the equation:

```
0 - 25 = -3/4x + 25 - 25
```

This simplifies to:

```
-25 = -3/4x
```

### Step 2: Isolate x

Now, we need to isolate *x* by getting rid of the coefficient **-3/4**. To do this, we'll multiply both sides of the equation by the reciprocal of **-3/4**, which is **-4/3**.

Multiplying both sides by **-4/3**:

```
(-4/3) * (-25) = (-4/3) * (-3/4x)
```

This simplifies to:

```
100/3 = x
```

### Step 3: Express the solution

Therefore, the solution to the equation **0 = -3/4x + 25** is **x = 100/3**.

### Conclusion

By following these simple steps, we successfully solved for *x* in the equation **0 = -3/4x + 25**. The solution is **x = 100/3**.